HYDRODYNAMIC AND MECHANIC RESPONSE OF A FLOATING FLEXIBLE ICE FLOE IN REGULAR WAVES WITH THE ICFD METHOD - Behnen, Jonas; von Bock und Polach, Rüdiger; von Bock und Polach, Franz; Klein, Marco; Ehlers, Sören (Volume 6: Polar and Arctic Sciences and Technology, 2022)
Climate change provides for a stronger wave climate and the open water area in this region will increase. The increase in open water area allows for an increase in higher energy surface waves than previously. In addition, human activities are much more complex in this zone, called Marginal Ice Zone, compared to the open ocean, so that there is an increased research interest in the physical processes of wave-ice interaction and the resulting statements on the influence on maritime technology. This work deals with the development of an efficient simulation environment for the 2D wave-ice interaction on the finite platform LSDYNA. The numerical model based on the coupled ICFD and implicit structural solvers of LS-DYNA. The motion behavior and the mechanical behavior of the ice floe due to the interaction with different waves are investigated. The stronger wave climate in the Marginal Ice Zone intensifies, making the waves more energetic and increasing the wave steepness. The results of the simulation clearly show that larger wave steepnesses have a large influence on the mechanical stress in the ice floe and the deflection increases. These mechanical stresses lead in the critical cases to a fracture of the ice floe into several smaller ice floes. Consideration of the ratio of ice floe length to wave length showed that the smaller the ratio, the larger the heave and surge movements of the ice floe induced by the waves.